PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA TUGU BANDUNG, KECAMATAN KABANDUNGAN, KABUPATEN SUKABUMI - Trihantana, Rully; Nurhasan, Abdul Khodir; Meizia, Revanda Shiva (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2025)
This community service aims to increase a good proportion of finances through sharia savings in Tugu Bandung Village, Kabandungan District, Sukabumi Regency. The subject of this community service is the people of Tugu Bandung Village, Kabandungan District, Sukabumi Regency, West Java Province. In this community service, activities are carried out based on the Participatory Action Researh (PAR) approach. The results of this community service show that public understanding of sharia savings still needs to be improved. This sharia savings plays an important role in the community and families in Tugu Bandung village in planning their finances better. This program not only helps families in managing their finances in a structured and halal way but also encourages a saving culture that is in accordance with Islamic values.